PENGARUH FAKTOR PENDIDIKAN, PELATIHAN DAN PENGALAMAN MENGAJAR TERHADAP PROFESIONALISME GURU SMA NEGERI I TORJUN KABUPATEN SAMPANG - Supriyadi Supriyadi; Chamariyah Chamariyah; Woro Utari (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 44 teachers. The objectives of this study are 1). To test and analyze the simultaneous influence of education, training and teaching experience on the professionalism of teachers at SMA Negeri I Torjun, Sampang Regency. 2). To test and analyze the partial influence of education, training and teaching experience on the professionalism of teachers at SMA Negeri I Torjun, Sampang Regency. 3.) To test and analyze the variables between education, training and teaching experience that have a dominant influence on the professionalism of teachers at SMA Negeri I Torjun, Sampang Regency. The results showed that 1.) Education, training and teaching experience simultaneously had a significant influence on teacher professionalism at SMA Negeri I Torjun, Sampang Regency. 2.) Education, training and teaching experience partially have a significant influence on teacher professionalism in SMA Negeri I Torjun, Sampang Regency. 3.). Teaching experience has a dominant influence on teacher professionalism at SMA Negeri I Torjun, Sampang Regency.